Sindrome de Kasabach-Merritt, una patología rara y potencialmente mortal en pediatría - Paz Amador, Kelly Johana; Jaimes Hernández, Laura Ximena (Revista Colombiana de Hematología y Oncología, 2023)
Abstract: A clinical case of a Kasabach-Merritt syndrome secondary to a kaposiform hemangioendothelioma in a 2-month-old child is presented, which was confirmed clinically, laboratory tests and magnetic resonance imaging. The expression of the disease was characterized by a rapidly growing vascular tumor on the left thigh that progressed to disseminated intravascular coagulation that was difficult to control, requiring multiple transfusions and pharmacological support to compensate for its life-threatening condition.